Experiences of parents of preterm children hospitalized regarding restrictions to interact with their children imposed because of the COVID-19 pandemic (2021)
ABSTRACT: Objective. To describe the experiences of parents of hospitalized preterm children regarding the restrictions implemented in the neonatal intensive care unit -NICUduring the COVID-19 pandemic. Methods. Qualitative study. Semi-structured interviews were conducted between April and October 2020 with 12 parents of preterm children, whose children were hospitalized and discharged from NICU during the pandemic. The analysis was performed with tools from grounded theory through open and axial coding. Results. The study identified four categories regarding the experience: 1) needing information: refers to the need for clear and close information to compensate for the physical distance; 2) limiting the interaction with the children: expressed as a painful situation, which minimizes opportunities for learning to care at home for their preterm child; 3) the pandemic: adding to the fears: in which the virus appears as a new threat for the children, who are vulnerable given their premature condition; and 4) limiting social support after discharge: identifies that the parents had less family and professional support for care after discharge during times of pandemic. Conclusion. Parents of preterm children lived a difficult experience that became complex within the context of the pandemic. The experiences of parents of preterm children during times of COVID-19 indicate that restrictions to enter neonatal units to prevent the virus transmission limited the interaction with the preterm child and with the health staff and increased the needs for information.